Mechanizm „poszukiwania wrogów” w zbiorowości społecznej jako wyraz patologii funkcjonowania instytucji. Ujęcie teoretyczno-metodologiczne - Leśniak-Moczuk, Arkadiusz (PRAWO i WIĘŹ, 2024)
The „secondary search” mechanism in a social community can be viewed as a symptom of the institution’s underlying pathology. It is a process whereby a problem arises or represents a threat to the opponent, while considering their accountability for various failures, difficulties or challenges facing the community. In order to gain access to scientific research, the extension of the „available search” is presented in two approaches. The first of these is analysed from a macrosocial point of view. This is an essential scientific presentation by Aaron Wildavsky, in which it is argued that the „enemy of effects” has full mobilisation effects. These effects help collective reactions to the perception of a threat. Furthermore, it is proposed that the „external enemy” can be caused by the cause of radical reforms. The second perspective is that of microsocial analysis, which is of great significance in a number of scientific fields. This includes the work of Muzafer Sherif, Vamik D. Volkan, Henri Tajfel and John C. Turner, Ervin Staub and Nick Haslam, who have demonstrated that the focus of the community on „searching for recipients” can mobilise them to achieve the goal. However, this is caused by issues and failures that have the potential to impede the development of the community, leading to stagnation or even regression.